Treatment - Hallett,J; Welton,T; Brandt-Talbot,A (2017)
The present disclosure relates to an improved method for treating a lignocellulose biomass in order to dissolve the lignin therein, while the cellulose does not dissolve. The cellulose pulp obtained can be used to produce glucose. In addition the lignin can be isolated for subsequent use in the renewable chemical industry.